Theoretical-methodological bases of international negotiation (Journal of Philosophy Culture and Political Science, 2015)
This article dedicated to the analyses of theoretical and methodologicalbases of international negotiation. World outlook and methodologicalbases of international negotiation consists the complex of philosophic andgeneral theoretical ideas about negotiation. Ideas of politics accumulatesin the analyses, approaches and orientations of international political cognition.In modern international negotiation exists various methodologicalconcepts of analyses of international negotiation process. One of thebranches of aforementioned science are theoretical and methodologicalbasis which helps to form international negotiations as a study or subjectand methods of searching which view international negotiations as a goalof science. This article says about the important and urgent role of internationalnegotiations in the field of world politics. The methodology ofinternational negotiations consists of several stages of formation. Thoughtsand hypotheses of scholars concerning the theoretical and methodologicalbasis of international negotiations are significant. Methods of understandingof American, European and Russian scholars helped to find out politicalreality through the international negotiations.
Keywords: international negotiation; function; method; theory; classification.